Handloom Cluster Development Program: A Case Study - Akoijam, Sunildro L. S. (Prabandhan: Indian Journal of Management, 2012)
This case is about YVU, a social organization which has been engaged in various development activities operating in Manipur for the last four decades. Manipur is a state where people depend mainly on agriculture for livelihood. Besides agriculture, handloom and weaving are the major sectors which provide a livelihood to various people of the state. This case focuses on the handloom development programme inducted by YVU, an NGO in Manipur at Nambol, Bishnupur District, Manipur. This study focuses on strategic initiatives taken up by YVU with financial support from SIDBI to meet the various objectives set by the organization. It also tries to identify the roles played by the industry in the development of the socio-cultural as well and economic condition of the state.